Gender, Science and Mathematics
XV, 230 p.
Keywords: Throughout the Western world, the relationship between gender, science and math ematics has emerged as critical in a variety of contexts. In tertiary institutions, the study of "gender issues", frequently with reference to science and mathematics, is of central significance to many disciplines. Gender studies are being offered as sepa rate courses or parts of existing courses in preservice and postgraduate teacher edu cation, women's studies, technology studies and policy studies. In addition, in the broader context of education at all levels from primary/elementary through to higher, concerned policy-makers and practitioners frequently focus on the interaction of gender, science and mathematics in their attempts to reform and improve education for all students. In all of these contexts, there is an urgent need for suitable texts, both to provide resources for teachers and students and to inform policy-makers and practitioners. This book has been developed specifically to meet this need. It is designed to be used throughout the world in a variety of tertiary courses and by policy-makers concerned with activities which interface with the gender/science/mathematics rela tionship. It provides examples which illustrate vividly the rich field from which practitioners and policy-makers in this area now can draw. Its particular appeal will stem from its practical approach and creative future perspective, the international renown of the authors and the generalisability of the recent research and thinking presented in each of the chapters.